Will the use of anabolic androgenic steroids become a significant cardiovascular risk factor in the future? - Pawłucki, Piotr; Maciak, Anna; Andrasz, Ewelina; Cuper, Paulina; Sekuła, Michał; Dziurowicz, Błażej (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Cardiovascular diseases are the leading cause of mortality in many European countries. Major modifiable risk factors include dyslipidemia, hypertension, smoking and diabetes. The aim of our study is to draw attention to the possible impact of the use of anabolic androgenic steroids on increased cardiovascular risk. Brief description of the state of knowledge: Currently, an increasing proportion of the population uses anabolic-androgenic steroids (AAS). This situation applies not only to athletes, but also to amateurs. The use of AAS may be associated with numerous complications. These include an increased risk of cardiovascular disease. The literature describes the effect of AAS use on the occurrence of dyslipidemia, insulin resistance, hypertension and metabolic syndrome. All these metabolic disorders result in increased cardiovascular risk. To prevent complications, it seems best to withdraw AAS gradually under medical supervision to minimize withdrawal effects. Conclusion: The use of AAS may cause cardiovascular disease, but additional long-term studies are needed to prove this. It is necessary to sensitize patients and doctors to the problem of AAS abuse in society, because this issue can become a significant risk factor for cardiovascular diseases in near future.